Episcleral Venous Fluid Wave in the Living Human Eye Adjacent to Microinvasive Glaucoma Surgery (MIGS) Supports Laboratory Research: Outflow is Limited Circumferentially, Conserved Distally, and Favored Inferonasally. Issue 2 (February 2019) - Fellman, Ronald L.; Grover, Davinder S.
Abstract : Purpose: The purpose of this study was to describe downstream patterns of outflow with the episcleral venous fluid wave (EVFW) in the living human eye adjacent to microinvasive glaucoma surgery (MIGS) and determine if the EVFW supports existing ex-vivo laboratory outflow research. Design: Retrospective, noncomparative case series. Patients: A total of 10 eyes of 10 patients who underwent phaco-Trabectome and 10 eyes of 10 patients who underwent phaco-iStent consecutively at Glaucoma Associates of Texas for cataract and uncontrolled glaucoma who demonstrated an episcleral wave. Methods: The EVFW was visualized and recorded during irrigation and aspiration. To describe the hydrodynamic properties of the fluid wave, its degrees, extent, and characteristics were measured with a protractor in Photoshop. Results: The incised Trabectome arc produced adjacent episcleral blanching of 134±11 degrees (range, 112 to 150 degrees) with an additional 54 degrees of marginal recruitment (41 degrees inferonasal plus 13 degrees superonasal) adjacent to the ends of the Trabectome incision. The mean episcleral blanch for the iStent was 51±19 degrees (range, 19 to 90 degrees), comprised of 29 degrees inferonasal plus 22 degrees superonasal. Conclusions: Downstream episcleral flow in the living human eye adjacent to the iStent is variable and mainly confined to 2 clock hours indicating a lack of significant circumferential flow in glaucomatous eyes. Flow distal to the Trabectome site encompasses the Trabectome incisional arc with an additional 2 clock hours of lateral fluid wave favoring the inferonasal over superonasal quadrant 3 to 1. These in-vivo findings made visible with MIGS, corroborate recent in-vivo and long-standing ex-vivo laboratory research that outflow is largely segmented, favored inferonasally and conserved distally.